Are plasma biomarkers of immune activation predictive of HIV progression: a longitudinal comparison and analyses in HIV-1 and HIV-2 infections? - Nyamweya, S; Townend, J; Zaman, A; Steele, S; Jeffries, D; Rowland-Jones, S; Whittle, H; Flanagan, K; Jaye, A (Public Library of Science, 2012)
BACKGROUND: Chronic immune activation is a hallmark of HIV infection and has been associated with disease progression. Assessment of soluble biomarkers indicating immune activation provide clues into pathogenesis and hold promise for the development of point-of-care monitoring of HIV in resource-poor-settings. Their evaluation in cohort resources is therefore needed to further their development and use in HIV research. METHODOLOGY/PRINCIPAL FINDINGS: Longitudinal evaluation of βeta-2 microglobulin (β-2 m), neopterin and suPAR soluble urokinase-type plasminogen activator receptor (suPAR) was performed with archived plasma samples to predict disease progression and provided the first direct comparison of levels in HIV-1 and HIV-2 infections. At least 2095 samples from 137 HIV-1 and 198 HIV-2 subjects with starting CD4% of ≥ 28 and median follow up of 4 years were analysed. All biomarkers were correlated negatively to CD4% and positively to viral load and to each other. Analyses in subjects living for ≥ 5 years revealed increases in median β-2 m and neopterin and decreases in CD4% over this period and the odds of death within 5 years were positively associated with baseline levels of β-2 m and neopterin. ROC analyses strengthened the evidence of elevation of biomarkers in patients approaching death in both HIV-1 and HIV-2 infections. Regression models showed that rates of biomarker fold change accelerated from 6-8 years before death with no significant differences between biomarker levels in HIV-1 and HIV-2 at equal time points prior to death.An 'immune activation index' analysis indicative of biomarker levels at equivalent viral loads also showed no differences between the two infections. CONCLUSIONS/SIGNIFICANCE: Our results suggest that β-2 m and neopterin are useful tools for disease monitoring in both HIV-1 and HIV-2 infections, whereas sUPAR performed less well. Levels of immune activation per amount of virus were comparable in HIV-1 and HIV-2 infected subjects.